Ethnic Specificity of Species and Strain Composition of Lactobacillus Populations From Mother–Infant Pairs, Uncovered by Multilocus Sequence Typing - Yuan, Lixia; Zhang, Xueling; Luo, Baolong; Li, Xu; Tian, Fengwei; Yan, Wenli; Ni, Yongqing (Frontiers in Microbiology, 2022)
The maternal gut is thought to be the principal source of potential probiotic bacteria in the infant gut during the lactation stage. It is not clear whether facultative symbiont lactobacilli strictly follows vertical transmission from mother to infant, and displays the ethnic specificity in term of species and strain composition in mother-infant cohort. In the present study, a total of sixteen former Lactobacillus species (365 strains) and eleven species (280 strains) were retrieved from thirty-one healthy mother-infant pairs of two ethnic groups, which have never intermarried, respectively. The result showed that the composition and number of Lactobacillus species between two ethnic groups varied. Among 106 Lacticaseibacillus paracasei strains isolated, 64 representative strains were classified into 27 sequence types (ST) by means of multilocus sequence typing, of which 20 STs derived from 33 Uighur strains, and 7 STs from 31 Li strains, and no homologous recombination event of genes was detected between strains of different ethnic groups. A go-EBURST analysis revealed that except for a few mother-infant pairs detected more than one sequence type, Lacticaseibacillus paracasei isolates from the same mother-infant pair were found to be monophyletic in most cases, confirming vertical transfer of Lactobacillus at the strain level. More notably, Lacticaseibacillus paracasei isolates from the same ethnic group were more likely than strains from another to be incorporated into a specific phylogenetic clade or clonal complex (CC) with similar metabolic profile of glycan, supporting the hypothesis of ethnic specificity to a large degree. Our study provides evidence for the development of personalized probiotic tailored to very homogenous localized population from the perspective of maternal and child health.